Using a stakeholder-engaged approach to develop and validate electronic clinical quality measures. (7th October 2016) - Herndon, Jill Boylston; Aravamudhan, Krishna; Stephenson, Ronald L; Brandon, Ryan; Ruff, Jesley; Catalanotto, Frank; Le, Huong
Abstract : Objective: To describe the stakeholder-engaged processes used to develop, specify, and validate 2 oral health care electronic clinical quality measures. Materials and Methods: A broad range of stakeholders were engaged from conception through testing to develop measures and test feasibility, reliability, and validity following National Quality Forum guidance. We assessed data element feasibility through semistructured interviews with key stakeholders using a National Quality Forum–recommended scorecard. We created test datasets of synthetic patients to test measure implementation feasibility and reliability within and across electronic health record (EHR) systems. We validated implementation with automated reporting of EHR clinical data against manual record reviews, using the kappa statistic. Results: A stakeholder workgroup was formed and guided all development and testing processes. All critical data elements passed feasibility testing. Four test datasets, representing 577 synthetic patients, were developed and implemented within EHR vendors' software, demonstrating measure implementation feasibility. Measure reliability and validity were established through implementation at clinical practice sites, with kappa statistic values in the "almost perfect" agreement range of 0.80–0.99 for all but 1 measure component, which demonstrated "substantial" agreement. The 2 validated measures were published in the United States Health Information Knowledgebase. Conclusion: The stakeholder-engaged processes used in this study facilitated a successful measure development and testing cycle. Engaging stakeholders early and throughout development and testing promotes early identification of and attention to potential threats to feasibility, reliability, and validity, thereby averting significant resource investments that are unlikely to be fruitful.